Jumping and non-jumping athletes land differently: implications for return to sport - Marks, J. P.; Tijssen, M.; el Hadouchi, M.; Janssen, I. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
Currently the LSI is used to determine whether an athlete is ready to return-to-sport (RTS). However, research shows that LSI inadequately identifies RTS readiness. Assuming that all athletes use the same landing strategy overlooks the potential variation between different sports. This study examines kinematic differences of the triple hop test between jumping and non-jumping athletes using inertial measurement units. Differences in landing kinematics between 18 male athletes (10 handball, 8 judo) were analysed. SPM analysis identified significant differences in trunk rotation and lateral flexion during landing. Notably, judokas demonstrated distinct movement patterns, related to emphasising sport-specific mechanics compared to handballers. These findings highlight the importance of integrating visual observation and motion capture, to better evaluate RTS readiness.